History of Philosophy, Science and Culture in Indian - Chattopadhyaya, D. P. (Debi Prasad), 1933-; Project of History of Indian Science, Philosophy, and Culture; Indian Council of Philosophical Research (New Delhi : Project of History of Indian Science, Philosophy, and Culture, 1995)
Contributed articles.
v. 1. Science, philosophy and culture in historical perspective -- v. 2. Some aspects of India's philosophical and scientific heritage -- v. 3. Mathematics, astronomy, and biology in Indian tradition, some conceptual preliminaries -- v. 4. Language, logic and science in India : some conceptual and historical perspectives.
"Sponsored by Indian Council of Philosophical Research."
Includes bibliographical references.
Keywords: Mathematics -- India -- History; Astronomy -- India -- History; Biology -- India -- History